المكون التداولي في كتابات "عبد الرحمان الحاج صالح - علاوة, زينب; رزقي, حورية (جامعة الوادي - university of Eloued, 2021)
للدكتور عبد الرحمن حاج صالح إسهامات جليلة في اللسانيات العربية، خصوصا في دراسته التّراث اللّغوي العربي، وتحديدا في مجالي البلاغة والتّداوليّة؛ حيث نجده يحلّل ويمحّص ما وقف عليه في هذا التّراث، ويقارن ذلك بما كتبه الباحثون الغربيون في هذا الشأن، ليقول في الأخير كلمته؛ ومدارها أنّ تراثنا العربي غنيّ بشتى العلوم، ثريّ بالنّظريات التي تواكب ما وصل إليه الغربيون في دراساتهم اللّسانية. سنحاول في هذه الدراسة أن نسلط الضوء على بعض ما تناولته كتب الدكتور عبد الرحمن الحاج صالح في كتاباته وخصوصا فيما تعلق بنظرته لعلم التداولية المستجد وربطه بما جاء في الكتب العربية التراثية وبما اسماه ظواهر التخاطب. Dr. Abd al-Rahman al-Hajj Salih has made great contributions in Arabic linguistics, especially in the study of linguistic heritage, exactly in the fields of rhetoric and pragmatics. Where are we find him analyzing and scrutinizing what he found in this heritage, and comparing that with what western scholars wrote in this regard, to say in the end his word, which is that our Arab heritage is rich with a various science, which matches a lot of theories that westerners have reached in their linguistic studies. In this study, we will try to spotlight on some of what was dealt with in the books of Dr. Abd al-Rahman al-Hajj Salih, especially with regard to his view of the emerging deliberative science and linking it to what was mentioned in the traditional Arabic books and what he called it phenomena of discourse.
مقال
Keywords: لسانيات؛ ; تداولية؛ ; عبد الرحمن الحاج صالح؛ ; دلالة؛ ; خطاب; linguistics; pragmatics; Abd al-Rahman al-Hajj Salih; Semantic; Discourse.